Pengaruh Adopsi Financial Technology dan Implementasi Blockchain Technology terhadap Volatilitas Harga Saham Bank Digital di Bursa Efek Indonesia - Sari, Amilia Paramita (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of Financial Technology (Fintech) adoption and Blockchain Technology implementation on stock price volatility in digital banks listed on the Indonesia Stock Exchange (IDX), focusing on Bank Jago (ARTO), Bank Neo Commerce (BBYB), and Bank Harda Internasional (BBHI). This study uses a quantitative approach with multiple linear regression analysis to test the hypothesis. Classical assumption tests, including the Shapiro-Wilk test and the ARCH/GARCH model, were conducted to ensure the validity of the regression model. The results of the hypothesis testing revealed that the adoption of Financial Technology has a positive and significant effect on stock price volatility. Conversely, the use of Blockchain Technology has a negative effect on stock price volatility,